PENETAPAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING DALAM MENENTUKAN HARGA JUAL KERIPIK USUS AYAM - Suryananda pradana putra widodo; Mochammad haichal miftah anhali; Muchassissurr rizky putra wardoyo; Ribangun bamban jakaria (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Companies must have the right strategies and methods so that their products can remain competitive with competitors' products and continue to generate profits. Therefore, determining the selling price of a product is based on the company's ability to calculate production costs for the products produced. The aim of this research is to calculate the production costs of MSME products in determining selling prices. The method used is full costing, Full costing is a method of determining production costs which consist of raw material costs, direct labor costs, and factory overhead costs, both variable and fixed. The results of this research are total production costs of Rp. 16.075.000 rupiah by producing 300 kilograms of chicken intestine chips. Calculating the cost of production using the full costing method, the value of the cost of production is IDR 53.583 per kilogram. The additional cost of profit or company margin is vulnerable to 10% to 20% with a rupiah value of Rp. 5.358,3- to 10.716,6,-.